Pengaruh Dukungan ORganisasi, Kejelasan Peran dan Kepemimpinan Terhadap Prestasi Kerja Karyawan Pada PT. Pagun Taka di Samarinda - Djoko Suseno; Yonathan Pongtuluran; Siti Maria (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The purpose of this study to determine the effect of organizational support, clarity of roles and leadership on employee performance PT mendenarkan tagun Taka in Samarinda. Elementary theory used human resource management by using multiple linear regression analysis with 33 samples.The conclusion of this study:Based on the calculation of the correlation coefficient (R) indicates that there is a very strong relationship between the Support organization, clarity of roles and leadership with job performance PT Pagun Taka In Samarinda, the coefficient of determination (R2) indicates that the variable support organization, clarity of roles and leadership is able to explain the dependent variable work performance and there are other variables that are not included in this study.Variable Support partially organization has a significant influence on employee job performance PT Pagun Taka In Samarinda., Variable partial role clarity has a significant influence on employee job performance PT Pagun Taka In Samarinda, partially Leadership variables have a significant effect on job performance Employee PT Pagun Taka In Samarinda Keywords: Support organization, Role Clarity, Leadership - Job Performance